Serotype distribution, antimicrobial susceptibility and molecular epidemiology of invasive Streptococcus pneumoniae in the nine-year period in Serbia - Opavski, Natasa; Jovicevic, Milos; Kabic, Jovana; Kekic, Dusan; Vasiljevic, Zorica; Tosic, Tanja; Medic, Deana; Laban, Suzana; Ranin, Lazar; Gajic, Ina (Frontiers in Microbiology, 2023)
Streptococcus pneumoniae is one of the leading bacterial pathogens that can cause severe invasive diseases. The aim of the study was to characterize invasive isolates of S. pneumoniae obtained during the nine-year period in Serbia before the introduction of the pneumococcal conjugate vaccines (PCVs) into routine vaccination programs by determining: serotype distribution, the prevalence and genetic basis of antimicrobial resistance, and genetic relatedness of the circulating pneumococcal clones. A total of 490 invasive S. pneumoniae isolates were included in this study. The serotype, antimicrobial susceptibility, and ST of the strains were determined by the Quellung reaction, disk- and gradient-diffusion methods, and multilocus sequence typing (MLST), respectively. The most common serotypes in this study were 3, 19F, 14, 6B, 6A, 19A, and 23F. The serotype coverages of PCV10 and PCV13 in children less than 2 years were 71.3% and 86.1%, respectively, while PPV23 coverage in adults was in the range of 85-96%, depending on the age group. Penicillin and ceftriaxone-non-susceptible isolates account for 47.6% and 16.5% of all isolates, respectively. Macrolide non-susceptibility was detected in 40.4% of isolates, while the rate of multidrug- and extensive-drug resistance was 20.0% and 16.9%, respectively. The MLST analysis of 158 pneumococci identified 60 different STs belonging to the 16 Clonal Complexes (CCs) (consisting of 42 STs) and 18 singletons. The most common CC/ST were ST1377, CC320, CC15, CC273, CC156, CC473, CC81, and CC180. Results obtained in this study indicate that the pre-vaccine pneumococcal population in Serbia is characterized by high penicillin and macrolides non-susceptibility, worrisome rates of MDR and XDR, as well as a high degree of genetic diversity. These findings provide a basis for further investigation of the changes in serotypes and genotypes that can be expected after the routine introduction of PCVs.